Abnormal Glucose Tolerance, White Blood Cell Count, and Telomere Length in Newly Diagnosed, Antidepressant-Naïve Patients with Depression - Garcia-Rizo, Clemente (2012)
Chronic mood disorders have been associated with a shortened telomere, a marker of increased mortality rate and ageing, and impaired cellular immunity. However, treatment may confound these relationships. We examined the relationship of glucose tolerance, white blood cell count and telomere length to depression in newly diagnosed, antidepressant-naïve patients. Subjects with major depression (n=15), and matched healthy control subjects (n=70) underwent a two-hour oral glucose tolerance test and evaluation of blood cell count and telomere content. The depression group had significantly higher two-hour glucose concentrations and a lower lymphocyte count than control subjects (respective means [SD] for two-hour glucose were 125.0 mg/dL [67.9] vs 84.6 [25.6] (p<.001); for lymphocyte count 2.1 × 10(9)/L [0.6] vs. 2.5 ×10(9)/L [0.7] p=.028).Telomere content was significantly shortened in the depression group (87.9 [7.6]) compared to control subjects (101.0 [14.3]; p<0.01). Abnormal glucose tolerance, lymphopenia and a shortened telomere are present early in the course of depression independently of the confounding effect of antidepressant treatment, supporting the concept of major depression as an accelerated ageing disease.